Analysis of pressure, angle and temporal effects on tissue optical properties from polarization-gated spectroscopic probe measurements - Ruderman, Sarah (Optical Society of America, 2010)
Noninvasive optical techniques for tissue characterization, in particular, light scattering properties and blood supply quantification of mucosa, is useful in a wide variety of applications. However, fiber-optic probes that require contact with the tissue surface can present a challenging problem in the variability of in vivo measurements due the nature of interactions, for example affects due to variations in pressure applied to the probe tip. We present an in vivo evaluation of pressure, angle, and temporal effects on tissue properties for polarization-gated spectroscopy at superficial depths (within 100 to 200 microns of tissue surface) for oral mucosa.